Dynamic performance of auxetic structures: experiments and simulation. (6th April 2020) - Alomarah, Amer; Xu, Shanqing; Masood, Syed H; Ruan, Dong
Abstract: In this study, the in-plane mechanical properties of auxetic structures subjected to dynamic compression have been investigated experimentally and numerically. The studied auxetic structures, which have negative Poisson's ratios, include a recently developed auxetic structure named re-entrant chiral auxetic (RCA) structure, re-entrant honeycomb, tetrachiral honeycomb and anti-tetrachiral honeycomb. All structures studied were fabricated from polyamide12 (PA12) powder using multi jet fusion. Compressive tests were conducted at a constant crushing velocity of 5 m s −1 on an Instron VHS 8800 high speed testing machine. The experimental results showed that the RCA structure crushed in the Y direction offered better energy absorption capacity than the other three types of honeycomb. It was also found that loading direction had a significant influence on deformation modes and auxetic features of the RCA structure, while it had a moderate influence on the energy absorption capacity. Numerical models were developed using ABAQUS/explicit and verified by experimental results. Parametric study was conducted to investigate the effects of crushing velocity and geometrical parameters on the dynamic performance of the RCA structure.